Relationship between Family Violence and Bullying Behaviour among Secondary School Students in Ilorin, Kwara State - OMOSHALEWA BADAMAS (International Journal of Advanced Humanities Research)
The study examined the relationship between family violence and bullying behaviour among secondary school students in Ilorin, Kwara State. The researcher employed a descriptive survey research design of correlation type. The study involved selected SSS 2 and SS 3 students in public secondary schools in the study area. A sample of 400 students was drawn from 20 randomly selected secondary schools. Research instrument tagged “Questionnaire on Family Violence and Bullying Behaviour among Students” with reliability coefficients of 0.73 and 0.76 for family violence sub-scale and bullying sub-scale respectively was used for data collection. The data collected was analysed using percentage and Pearson Product Moment Correlation (PPMC). The formulated hypothesis was tested at 0.05 level of significance. The result of the study showed that the level of family violence experienced by secondary school students was low; the level of bullying behaviour among secondary school students was low; and that there was significant relationship between family violence and bullying behaviour among secondary school students in Ilorin, Kwara State. The study concludes that family violence promotes bullying behaviour. It was recommended among others that generalized bullying behaviour from school to home should be corrected and managed consistently for maximum effectiveness for correction.